2005
DOI: 10.1073/pnas.0408529102
|View full text |Cite
|
Sign up to set email alerts
|

Replication and packaging of Norwalk virus RNA in cultured mammalian cells

Abstract: Human noroviruses, the most common cause of nonbacterial gastroenteritis, are characterized by high infectivity rate, low infectious dose, and unusually high stability outside the host. However, human norovirus research is hindered by the lack of a cell culture system and a small animal model of infection. Norwalk virus (NV) is the prototype strain of human noroviruses. We report here replication of NV viral RNA and its packaging into virus particles in mammalian cells by intracellular expression of native for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 39 publications
1
75
0
1
Order By: Relevance
“…First, they show that authentic U201 RNA is produced and that the sequence of the subgenomic RNA generated by this reverse genetics system is identical to the predicted native subgenomic RNA. This finding confirms results from the MVA/T7 system that expressed the NV genome (10). Second, they show that progeny virus with a similar density to native virions (11) contains not only the predicted VP1, VP2, and genomic RNA but also, VPg (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…First, they show that authentic U201 RNA is produced and that the sequence of the subgenomic RNA generated by this reverse genetics system is identical to the predicted native subgenomic RNA. This finding confirms results from the MVA/T7 system that expressed the NV genome (10). Second, they show that progeny virus with a similar density to native virions (11) contains not only the predicted VP1, VP2, and genomic RNA but also, VPg (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Gnotobiotic pigs can support replication of a HuNoV genogroup II (GII) strain with the occurrence of mild diarrhea, fecal virus shedding, and immunofluorescent (IF) detection of both structural and nonstructural proteins in enterocytes (9). Previous systems to express the HuNoV genome from cloned DNA using T7/vaccinia systems showed that mammalian cells can produce progeny virus (10,11), but these systems are not sufficiently efficient to be widely used to propagate HuNoVs in vitro. The factors responsible for the block(s) of viral replication using standard cell culture systems remain unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of porcine SaV Cowden strain was delineated in gnotobiotic pigs [19,20]. Most recently, reverse genetic systems were generated for the porcine Cowden SaV and the human Norwalk NoV, in which infectious viral particles were rescued after replication of the viral genomic RNA [35,36]. In spite of these advances, most NoVs and SaVs remain refractory to growth in cell culture and extensive efforts to propagate them in vitro have failed [37].…”
Section: History Of Enteric Caliciviruses and The Discovery Of Pormentioning
confidence: 99%
“…The human caliciviruses, including the prototype Norwalk virus, have yet to be fully propagated in tissue culture, although recent results suggest that limited genome replication and encapsidation can occur using a vaccinia virus-driven expression system (12). In contrast to the human caliciviruses, feline calicivirus (FCV), porcine enteric calicivirus (13,14), and murine norovirus 1 (MNV) (15) can be propagated in tissue culture.…”
mentioning
confidence: 99%